Oil-soluble ionic liquid with anti-corrosion and anti-friction performance as well as preparation method and application of oil-soluble ionic liquid

By designing and preparing the functionalized quaternary phosphine ionic liquid of benzotriazole, the problems of high preparation cost, corrosive metals and poor compatibility of existing ionic liquids are solved, and excellent friction reduction and wear resistance to steel/steel friction pairs are achieved. and corrosion resistance, good oil solubility and environmental protection benefits.

CN119431446AActive Publication Date: 2025-02-14LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1

Patent Information

Application Number
CN202411572250.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

As lubricant additives, existing ionic liquids have high preparation costs, corrosive metal substrates and poor compatibility with commonly used lubricating oils, which limits their industrial applications.

Method used

By designing and preparing quaternary phosphonium ionic liquids functionalized by benzotriazole, using different alkyl chain long-square phosphonium cations and diisooctyl succinate sodium sulfonate as anions, they were prepared by quaternary phosphonium ionization reaction and ion exchange reaction Oil-soluble ionic liquid with anti-corrosion and friction reduction properties are produced.

Benefits of technology

It achieves excellent friction reduction and wear resistance and good corrosion resistance to steel/steel friction pairs, and has good oil solubility and environmental protection benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431446A_ABST
    Figure CN119431446A_ABST
Patent Text Reader

Abstract

The invention provides an oil-soluble ionic liquid with anti-corrosion and anti-friction performance and a preparation method and application of the oil-soluble ionic liquid. Cation of the oil-soluble ionic liquid is quaternary phosphonium cation with different alkyl chain lengths and benzotriazole functional groups, and anion of the oil-soluble ionic liquid is dioctyl sodium sulfosuccinate. The preparation method of the ionic liquid comprises the following steps: mixing chloromethyl benzotriazole and trioctylphosphine, and carrying out quaternary phosphonium reaction to obtain benzotriazole functionalized trioctylphosphonium; and mixing the benzotriazole functionalized trioctylphosphonium with docusate sodium, and carrying out an ion exchange reaction to obtain the oil-soluble ionic liquid. The oil-soluble ionic liquid serves as a lubricating additive of base oil PAO10 and is applied to lubrication of a steel / steel friction pair, and experimental results show that the oil-soluble ionic liquid has good solubility in the base oil PAO10, has excellent antifriction and antiwear performance on a steel / steel friction pair interface and also has a good corrosion inhibition effect on the friction pair interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lubricating materials, and in particular to an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties, and a preparation method and application thereof. Background Art

[0002] As an important member of the lubrication system, lubricating grease plays a vital role in different service conditions. However, with the continuous development of modern aerospace and space technology, new requirements have been put forward for the lubrication performance of lubricating grease. Traditional lubricating grease can no longer meet the lubrication and protection requirements of lubricated parts under harsh conditions. For this reason, the design and synthesis of new and efficient lubricants have attracted more and more attention. The applicant's research group first reported in 2001 that this type of material with low volatility, non-flammability, high thermal stability, low melting point and good electrical conductivity has excellent lubricating performance as a lubricant (CF Ye, WM Liu, YX Chen, et al, Chem. Commu, 21 (2001) 2244-2245.).

[0003] Since then, the scientific research on ionic liquids as lubricants and additives has become an independent new research direction and has attracted extensive attention from international peers. The applicant's research group has long been committed to the synthesis and performance research of functionalized ionic liquids. The applicant grafted phosphate functional groups onto imidazole rings by means of molecular design. The prepared ionic liquids showed a relatively efficient lubrication performance for metallic aluminum (ZGMu, F.Zhou, SXZhang, et al, Tribol.Inter.2005,38(8),725-731.). Although ionic liquids have better friction reduction and anti-wear properties than other synthetic lubricants, in the application research process of ionic liquids, it was found that there are still some problems as lubricant additives, such as high preparation cost, corrosion of metal substrates, poor compatibility with commonly used lubricants, etc., which greatly restrict its industrial application. After investigation, it was found that there are currently few reports on functionalized ionic liquids with good corrosion resistance and oil solubility. The applicant synthesized a class of quaternary phosphonium salt ionic liquids earlier and used them as lubricants for steel / aluminum friction pairs, proving that they have good anti-friction and anti-wear capabilities (XQ Liu, F. Zhou, YM Liang, et al, Wear 261 (2006) 1174–1179). We wondered whether we could improve their oil solubility by changing the alkyl chain length and improve their corrosion resistance as a base oil by grafting benzotriazole functional groups. To this end, combined with previous work, we designed and prepared a series of benzotriazole-functionalized quaternary phosphonium salt ionic liquids, which can effectively reduce the corrosion of base oil to metals, inhibit the formation of carbon deposits, and improve the lubrication properties of base oils. Summary of the invention

[0004] The present application provides an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties, and a preparation method and application thereof, to solve the above-mentioned problems mentioned in the background technology.

[0005] On the one hand, the present application provides an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties, wherein the oil-soluble ionic liquid has the following general formula:

[0006]

[0007] Wherein R and R1 are independently selected from C1-C 18 of alkyl.

[0008] Optionally, R and R1 are independently selected from any one of methyl, ethyl, propyl, butyl, isobutyl, pentyl, isopentyl, octyl, isooctyl, decyl, isodecyl, dodecyl, tetradecyl, hexadecyl and octadecyl.

[0009] On the other hand, the present application provides a method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties, which is used to prepare the above-mentioned oil-soluble ionic liquid, and the preparation method comprises the following steps:

[0010] (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole;

[0011] (2) washing the crude product of trioctylphosphonium functionalized with benzotriazole with an organic solvent for multiple times to obtain trioctylphosphonium functionalized with benzotriazole;

[0012] (3) The benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile are mixed and then subjected to an ion exchange reaction to obtain a benzotriazole-functionalized quaternary phosphonium salt ionic liquid, i.e., an oil-soluble ionic liquid.

[0013] Optionally, the molar ratio of chloromethylbenzotriazole to trioctylphosphine is 1:1-1.3.

[0014] Optionally, the conditions for the quaternization reaction are: heating under reflux at 80-85° C. for 24 hours.

[0015] Optionally, the organic solvent used to wash the crude product of trioctylphosphonium functionalized with benzotriazole is petroleum ether or n-hexane.

[0016] Optionally, the ion exchange reaction is carried out under reflux at 80-90° C. for 24-48 hours.

[0017] Optionally, the molar ratio of benzotriazole-functionalized trioctylphosphonium to docusate sodium is 1:1-1.2.

[0018] Optionally, the ion exchange reaction further comprises:

[0019] After the ion exchange reaction, a crude oil-soluble ionic liquid is obtained. The crude oil-soluble ionic liquid is subjected to reduced pressure distillation, the obtained heavy phase is dissolved in dichloromethane, washed with water for multiple times, separated into layers, and the obtained organic phase is dried to obtain a quaternary phosphonium salt ionic liquid functionalized with benzotriazole.

[0020] On the other hand, the present application provides an application of an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties, wherein the oil-soluble ionic liquid is the above-mentioned oil-soluble ionic liquid, or the oil-soluble ionic liquid prepared by the above-mentioned preparation method, and the oil-soluble ionic liquid is used as a lubricating material.

[0021] The oil-soluble ionic liquid with anti-corrosion and anti-friction properties provided in the present application and its preparation method and application realize the preparation of the oil-soluble ionic liquid, and the ionic liquid has not only excellent anti-friction and anti-wear properties for steel / steel friction pairs, but also good anti-corrosion properties. Compared with the prior art, it has the following beneficial effects:

[0022] (1) The cation of the oil-soluble ionic liquid provided in the present application is a quaternary phosphonium cation with different alkyl chain lengths of a benzotriazole functional group, and the anion is sodium diisooctyl sulfosuccinate. The introduction of the benzotriazole group can not only improve the stability of the ionic liquid, but also help the ionic liquid to form a stable lubricating film on the friction pair surface, which is beneficial to improve the load-bearing performance of the ionic liquid. At the same time, the quaternary phosphonium salt ionic liquid is functionalized by benzotriazole, and the π electrons in the benzotriazole and the empty d orbits on the iron surface can form a coordinated π-d conjugated effect adsorbed on the substrate surface to form a protective film, and the benzotriazole ring and long carbon chain structure unique to the ionic liquid can effectively isolate the corrosive environment, thereby preventing the corrosion of iron. By adopting quaternary phosphonium cations with different alkyl chain lengths, the ionic liquid has good oil solubility, which helps the ionic liquid to be fully dissolved in the base oil, and further improves the friction and wear resistance of the ionic liquid. Therefore, the present application functionalizes the quaternary phosphonium salt ionic liquid by benzotriazole, so that the ionic liquid has excellent tribological properties and can further improve the anti-corrosion performance of the ionic liquid.

[0023] (2) The oil-soluble ionic liquid is used as a lubricating additive for the base oil PAO10 and is applied to the lubrication of steel / steel friction pairs. The experimental results show that the oil-soluble ionic liquid has good solubility in the base oil PAO10 and has not only excellent friction reduction and anti-wear properties on the steel / steel friction pair interface, but also a good corrosion inhibition effect on the friction pair interface.

[0024] (3) The oil-soluble ionic liquid provided in the present application does not contain halogen, has no corrosion to the surface of metal friction pairs, is environmentally friendly, and has good environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 A thermal decomposition temperature diagram of the ionic liquid lubricating composition provided in Example 4 to Example 6 of the present application;

[0027] Figure 2 This is the Tafel plot of the ionic liquid lubricating composition provided in Example 6 of the present application. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0029] The present application provides an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties, and the oil-soluble ionic liquid has the following general formula:

[0030]

[0031] Wherein R and R1 are independently selected from C1-C 18 of alkyl.

[0032] Specifically, quaternary phosphonium salt ionic liquid, as a new type of lubricant, has the characteristics of extremely low volatility, good thermal stability and good viscosity-temperature property. The cation of the oil-soluble ionic liquid provided in the present application is a quaternary phosphonium cation with different alkyl chain lengths of benzotriazole functional groups, and the anion is sodium diisooctyl sulfosuccinate, and the introduction of benzotriazole groups can not only improve the stability of the ionic liquid, but also help the ionic liquid to form a stable lubricating film on the friction pair surface, which is conducive to improving the load-bearing performance of the ionic liquid. At the same time, by benzotriazole, the quaternary phosphonium salt ionic liquid is functionalized, and the π electrons in benzotriazole and the empty d orbits of the iron surface can form a coordinated π-d conjugated effect adsorbed on the substrate surface to form a protective film, and the benzotriazole ring and long carbon chain structure unique to the ionic liquid can effectively isolate the corrosive environment, thereby preventing the corrosion of iron. By adopting different alkyl chain length quaternary phosphonium cations, the ionic liquid is made to have good oil solubility, which helps the ionic liquid to be fully dissolved in the base oil, and further improves the friction and wear resistance of the ionic liquid. Therefore, the present invention functionalizes the quaternary phosphonium salt ionic liquid by benzotriazole, so that the ionic liquid has excellent tribological properties and can further improve the anti-corrosion performance of the ionic liquid. In addition, the ionic liquid does not contain halogens, does not corrode the surface of the metal friction pair, is environmentally friendly, and has good environmental benefits.

[0033] Optionally, R and R1 are independently selected from any one of methyl, ethyl, propyl, butyl, isobutyl, pentyl, isopentyl, octyl, isooctyl, decyl, isodecyl, dodecyl, tetradecyl, hexadecyl and octadecyl.

[0034] Specifically, ionic liquids synthesized with different alkyl chain lengths can be dissolved in different base oils, which helps to ensure the uniformity of the ionic liquid and base oil mixed system, and further helps to form a uniform and stable boundary lubrication film on the surface of the friction pair during the friction process, which is beneficial to achieve better friction reduction, anti-wear and corrosion inhibition on the interface.

[0035] The present application provides a method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties, which is used to prepare the above-mentioned oil-soluble ionic liquid. The preparation method comprises the following steps:

[0036] (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole;

[0037] (2) washing the crude product of trioctylphosphonium functionalized with benzotriazole with an organic solvent for multiple times to obtain trioctylphosphonium functionalized with benzotriazole;

[0038] (3) The benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile are mixed and then subjected to an ion exchange reaction to obtain a benzotriazole-functionalized quaternary phosphonium salt ionic liquid, i.e., an oil-soluble ionic liquid.

[0039] Specifically, the preparation reaction equation of the oil-soluble ionic liquid of the present application is as follows:

[0040]

[0041] Acetonitrile is used as the reaction solvent. Chloromethylbenzotriazole and trioctylphosphine are mixed and then subjected to quaternization reaction. After the reaction is completed, the mixture is cooled to room temperature to obtain a crude product of trioctylphosphonium functionalized with benzotriazole. The crude product is then washed with an organic solvent for multiple times to remove the unreacted raw materials in the quaternization reaction, thereby obtaining trioctylphosphonium functionalized with benzotriazole, which is named BTAP888Cl. Trioctylphosphonium functionalized with benzotriazole, sodium docusate and acetonitrile are mixed and subjected to ion exchange reaction to obtain an oil-soluble ionic liquid whose cation is a quaternary phosphonium cation with different alkyl chain lengths and an anion is sodium diisooctyl succinate sulfonate, i.e., a quaternary phosphonium salt ionic liquid functionalized with benzotriazole, which is named BTAP888-DOSS. The introduction of the benzotriazole group can not only improve the stability of the ionic liquid, but also help the ionic liquid to form a stable lubricating film on the surface of the friction pair, which is beneficial to improving the load-bearing performance of the ionic liquid. The π electrons in benzotriazole and the empty d orbitals on the iron surface can form a coordinated π-d conjugated effect and adsorb on the substrate surface to form a protective film, and the benzotriazole ring and long carbon chain structure unique to ionic liquids can effectively isolate the corrosive environment, thereby preventing the corrosion of iron. By using quaternary phosphonium cations with different alkyl chain lengths, the ionic liquid has better oil solubility, which helps the uniformity of the ionic liquid and base oil mixed system, and is beneficial to play a better role in reducing friction, anti-wear and corrosion inhibition on the interface.

[0042] The present application realizes the preparation of an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties through the above scheme. The cation of the oil-soluble ionic liquid is a quaternary phosphonium cation with different alkyl chain lengths of a benzotriazole functional group, and the anion is sodium diisooctyl sulfosuccinate. The benzotriazole functionalized trioctyl phosphonium is obtained by mixing chloromethyl benzotriazole and trioctyl phosphine, and then performing a quaternary phosphonium reaction. The benzotriazole functionalized trioctyl phosphonium is then subjected to an ion exchange reaction with sodium docusate to obtain the oil-soluble ionic liquid. The introduction of the benzotriazole group can not only improve the stability of the ionic liquid, but also help the ionic liquid to form a stable lubricating film on the surface of the friction pair, which is beneficial to improving the load-bearing performance of the ionic liquid. The benzotriazole ring and long carbon chain structure unique to the ionic liquid can effectively isolate the corrosive environment, thereby preventing the corrosion of iron. By using quaternary phosphonium cations with different alkyl chain lengths, the ionic liquid has better oil solubility, which helps the ionic liquid to fully dissolve in the base oil, further improving the friction reduction and anti-wear performance of the ionic liquid. The ionic liquid has not only excellent friction reduction and anti-wear performance for steel / steel friction pairs, but also good anti-corrosion performance

[0043] Optionally, the molar ratio of chloromethylbenzotriazole to trioctylphosphine is 1:1-1.3.

[0044] Optionally, the conditions for the quaternization reaction are: heating under reflux at 80-85° C. for 24 hours.

[0045] Specifically, the appropriate molar ratio of chloromethylbenzotriazole to trioctylphosphine can ensure that the quaternary phosphonium reaction is fully carried out. The temperature of the quaternary phosphonium reaction is preferably 85°C.

[0046] In the quaternization reaction, there is no special limitation on the amount of the reaction solvent acetonitrile. Furthermore, the ratio of chloromethylbenzotriazole to acetonitrile is preferably 1 mol: (150-200) mL.

[0047] Optionally, the organic solvent used to wash the crude product of trioctylphosphonium functionalized with benzotriazole is petroleum ether or n-hexane.

[0048] The amount of the organic solvent used in the washing process is not particularly limited. Specifically, the weight ratio of the crude trioctylphosphonium product functionalized with benzotriazole to the organic solvent is 1:3-5, and the organic solvent is washed three times on average.

[0049] Optionally, the ion exchange reaction is carried out under reflux at 80-90° C. for 24-48 hours.

[0050] Optionally, the molar ratio of benzotriazole-functionalized trioctylphosphonium to docusate sodium is 1:1-1.2.

[0051] Specifically, the molar ratio of benzotriazole-functionalized trioctylphosphonium to docusate sodium is preferably 1:1.2, and the temperature of the ion exchange reaction is preferably 85°C.

[0052] In the ion exchange reaction, there is no special limitation on the amount of the reaction solvent acetonitrile. Furthermore, the ratio of benzotriazole-functionalized trioctylphosphonium to acetonitrile is preferably 1 mol: (150-180) mL.

[0053] Optionally, the ion exchange reaction further comprises:

[0054] After the ion exchange reaction, a crude oil-soluble ionic liquid is obtained. The crude oil-soluble ionic liquid is subjected to reduced pressure distillation, the obtained heavy phase is dissolved in dichloromethane, washed with water for multiple times, separated into layers, and the obtained organic phase is dried to obtain a quaternary phosphonium salt ionic liquid functionalized with benzotriazole.

[0055] Specifically, the crude oil-soluble ionic liquid also contains impurities such as reaction solvent and unreacted raw materials, which need to be purified. First, the acetonitrile in the crude oil-soluble ionic liquid is removed by vacuum distillation, and the heavy phase obtained after vacuum distillation is dissolved in dichloromethane and washed with water for many times, and the oil-soluble ionic liquid is dissolved in dichloromethane and the impurities are dissolved in the aqueous phase. Wherein, the weight ratio of the heavy phase obtained after vacuum distillation to dichloromethane is 1:1.5-3, the weight ratio of the heavy phase to water is 1:2.5-3.5, and the washing water is washed three times on average.

[0056] The organic phase is dried with anhydrous sodium sulfate for 10-24 hours to remove the water in the organic phase, and then the dried organic phase is filtered to remove the anhydrous sodium sulfate, and finally the reduced pressure distillation is performed again to remove the dichloromethane to obtain an oil-soluble ionic liquid, i.e., a quaternary phosphonium salt ionic liquid functionalized with benzotriazole. The amount of anhydrous sodium sulfate used is: 10-15 g of anhydrous sodium sulfate per 100 mL of organic phase.

[0057] The above-mentioned process of removing organic solvent by vacuum distillation is a commonly used and mature impurity removal method in the art. Those skilled in the art are capable of adjusting the operating parameters in the vacuum distillation according to the actual solvent to be distilled, which will not be described in detail here.

[0058] The present application provides an application of an oil-soluble ionic liquid with anti-corrosion and friction-reducing properties. The oil-soluble ionic liquid is the above-mentioned oil-soluble ionic liquid, or an oil-soluble ionic liquid prepared by the above-mentioned preparation method. The oil-soluble ionic liquid is used as a lubricating material.

[0059] The oil-soluble ionic liquid provided in the present application is used as a lubricant additive for steel / steel friction pairs, and has a good friction reduction, anti-wear and corrosion inhibition effect on the interface of the steel / steel friction pair.

[0060] The following are embodiments of the present invention and effect test examples, and the technical scheme and technical effect of the present invention are further described, but the protection scope of the present invention is not limited to these embodiments. Any changes or equivalent substitutions that do not deviate from the concept of the present invention are within the protection scope of the present invention. In addition, those who do not indicate specific technical operation steps or conditions in the embodiments are all carried out according to the technology or conditions described in the general literature in this area or according to the product specification. Those who do not indicate the manufacturer of the reagents or instruments used are all conventional products that can be obtained commercially.

[0061] Example 1

[0062] An oil-soluble ionic liquid with anti-corrosion and friction-reducing properties and a preparation method thereof, comprising the following steps:

[0063] (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole;

[0064] The molar ratio of chloromethylbenzotriazole to trioctylphosphine is 1:1, the amount ratio of chloromethylbenzotriazole to acetonitrile is 1 mol:150 mL, and the conditions of the quaternization reaction are: heating under reflux at 80°C for 24 hours.

[0065] (2) The crude product of trioctylphosphonium functionalized with benzotriazole was washed with petroleum ether for several times to obtain trioctylphosphonium functionalized with benzotriazole, which was named as BTAP888Cl-1;

[0066] The weight ratio of the crude trioctylphosphonium product functionalized with benzotriazole to the organic solvent is 1:3.

[0067] (3) Mixing benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile and subjecting them to ion exchange reaction to obtain a crude benzotriazole-functionalized quaternary phosphonium salt ionic liquid, wherein the molar ratio of benzotriazole-functionalized trioctylphosphonium to sodium docusate is preferably 1:1, the amount ratio of benzotriazole-functionalized trioctylphosphonium to acetonitrile is preferably 1 mol:150 mL, and the ion exchange reaction is refluxed at 80°C for 24 hours.

[0068] First, acetonitrile in the crude oil-soluble ionic liquid is removed by vacuum distillation. The heavy phase obtained after vacuum distillation is dissolved in dichloromethane and washed with water for multiple times. The oil-soluble ionic liquid is dissolved in dichloromethane and the impurities are dissolved in the aqueous phase. The organic phase is dried with anhydrous sodium sulfate for 24 hours to remove the water in the organic phase. The dried organic phase is filtered to remove the anhydrous sodium sulfate. Finally, vacuum distillation is performed again to remove dichloromethane to obtain an oil-soluble ionic liquid, i.e., a quaternary phosphonium salt ionic liquid functionalized with benzotriazole, named BTAP888-DOSS-1.

[0069] The weight ratio of the heavy phase obtained after the reduced pressure distillation to dichloromethane is 1:1.5, the weight ratio of the heavy phase to water is 1:2.5, and the washing water is washed three times on average. The amount of anhydrous sodium sulfate used is: 10 g of anhydrous sodium sulfate per 100 mL of organic phase.

[0070] The molecular structure of the BTAP888-DOSS sample is as follows:

[0071]

[0072] Example 2

[0073] An oil-soluble ionic liquid with anti-corrosion and friction-reducing properties and a preparation method thereof, comprising the following steps:

[0074] (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole;

[0075] The molar ratio of chloromethylbenzotriazole to trioctylphosphine is 1:1.2, the amount ratio of chloromethylbenzotriazole to acetonitrile is 1 mol:170 mL, and the conditions of the quaternization reaction are: heating under reflux at 85°C for 24 hours.

[0076] (2) washing the crude product of trioctylphosphonium functionalized with benzotriazole with petroleum ether for multiple times to obtain trioctylphosphonium functionalized with benzotriazole, named BTAP888Cl-2;

[0077] The weight ratio of the crude trioctylphosphonium product functionalized with benzotriazole to the organic solvent is 1:4.

[0078] (3) Mixing benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile and subjecting them to ion exchange reaction to obtain a crude benzotriazole-functionalized quaternary phosphonium salt ionic liquid, wherein the molar ratio of benzotriazole-functionalized trioctylphosphonium to sodium docusate is preferably 1:1.2, the amount ratio of benzotriazole-functionalized trioctylphosphonium to acetonitrile is preferably 1 mol:165 mL, and the ion exchange reaction is carried out under heating reflux at 85°C for 48 hours.

[0079] First, acetonitrile in the crude oil-soluble ionic liquid is removed by vacuum distillation, and the heavy phase obtained after vacuum distillation is dissolved in dichloromethane and washed with water for multiple times, and the oil-soluble ionic liquid is dissolved in dichloromethane, and the impurities are dissolved in the aqueous phase. The organic phase is dried with anhydrous sodium sulfate for 24 hours to remove the water in the organic phase, and then the dried organic phase is filtered to remove the anhydrous sodium sulfate, and finally vacuum distillation is performed again to remove dichloromethane to obtain an oil-soluble ionic liquid, that is, a quaternary phosphonium salt ionic liquid functionalized with benzotriazole, named BTAP888-DOSS-2.

[0080] The weight ratio of the heavy phase obtained after the reduced pressure distillation to dichloromethane is 1:2.5, the weight ratio of the heavy phase to water is 1:3, and the washing water is washed three times on average. The amount of anhydrous sodium sulfate used is: 12 g of anhydrous sodium sulfate per 100 mL of organic phase.

[0081] Example 3

[0082] An oil-soluble ionic liquid with anti-corrosion and friction-reducing properties and a preparation method thereof, comprising the following steps:

[0083] (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole;

[0084] The molar ratio of chloromethylbenzotriazole to trioctylphosphine is 1:1.3, the dosage ratio of chloromethylbenzotriazole to acetonitrile is 1 mol:200 mL, and the conditions of the quaternization reaction are: heating under reflux at 85° C. for 24 h.

[0085] (2) washing the crude product of trioctylphosphonium functionalized with benzotriazole with petroleum ether for several times to obtain trioctylphosphonium functionalized with benzotriazole, named as BTAP888Cl-3;

[0086] The weight ratio of the crude trioctylphosphonium product functionalized with benzotriazole to the organic solvent is 1:5.

[0087] (3) Mixing benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile, and then subjecting the mixture to an ion exchange reaction to obtain a crude benzotriazole-functionalized quaternary phosphonium salt ionic liquid, wherein the molar ratio of benzotriazole-functionalized trioctylphosphonium to sodium docusate is preferably 1:1.2, the amount ratio of benzotriazole-functionalized trioctylphosphonium to acetonitrile is preferably 1 mol:180 mL, and the ion exchange reaction is carried out under heating reflux at 85°C for 48 hours.

[0088] First, acetonitrile in the crude oil-soluble ionic liquid is removed by vacuum distillation, and the heavy phase obtained after vacuum distillation is dissolved in dichloromethane and washed with water for multiple times, and the oil-soluble ionic liquid is dissolved in dichloromethane, and the impurities are dissolved in the aqueous phase. The organic phase is dried with anhydrous sodium sulfate for 24 hours to remove the water in the organic phase, and then the dried organic phase is filtered to remove the anhydrous sodium sulfate, and finally vacuum distillation is performed again to remove dichloromethane to obtain an oil-soluble ionic liquid, that is, a quaternary phosphonium salt ionic liquid functionalized with benzotriazole, named BTAP888-DOSS-3.

[0089] The weight ratio of the heavy phase obtained after the reduced pressure distillation to dichloromethane is 1:3, the weight ratio of the heavy phase to water is 1:3.5, and the washing water is washed three times on average. The amount of anhydrous sodium sulfate used is: 15 g of anhydrous sodium sulfate per 100 mL of organic phase.

[0090] Experimental Example 1

[0091] Structural Characterization of Oil-soluble Ionic Liquids

[0092] The oil-soluble ionic liquid obtained by the technical solutions provided in Examples 1 to 3 was subjected to nuclear magnetic resonance 1 H NMR, 13 C NMR, 31 P NMR and high-resolution mass spectrometry HRMS characterization results show that Examples 1-3 all achieve the preparation of oil-soluble ionic liquids, wherein the characterization data of Example 2 are as follows:

[0093] 1H NMR (400MHz, CDCl3) δ: 8.31 (d, J = 4.0Hz, 1H), 8.01 (d, J = 4.0Hz, 1H), 7.63 (t, J = 8.0Hz, 1H), 7.41 (t, J = 8.0Hz, 1H), 6.06 (s, 2H), 4.2 0(dd,J1=12.0Hz,J2=4.0Hz,1H),4.03-3.88(m,4H),3.32-3.13(m,2H),2.47-2.40(m,6H),1.72-1.17(m,54H),0.87-0.77(m,21H). 13 C NMR(100MHz, CDCl3)δ:171.65,169.28,145.40,134.18,134.16,129.68,125.27,119.70,11 1.27,67.88,67.19,62.07,39.58,39.06,38.78,38.76,38.64,38.57,34.30,31.72,30.84,3 0.69,30.41,30.37,30.11,29.16,29.13,29.01,28.98,28.94,28.91,28.85,23.75,23.48,23.05,22.71,22.64,21.73,21.69,18.79,18.36,14.14,14.12,11.04,11.00,10.87,10.83. 31 P NMR (162MHz,CDCl3)δ:35.10(s).Theoretical calculation value of cation:502.4285,actual measured value of cation:502.4263[C 31 H 57 N3P] + , anion theoretical calculated value: 421.2265, anion actual measured value: 421.2275 [C 20 H 37 O7S] - .

[0094] Experimental Example 2

[0095] Solubility test of oil-soluble ionic liquids

[0096] The solubility of the oil-soluble ionic liquid BTAP888-DOSS-2 obtained by the technical solution provided in Example 2 in the base oil PAO10 was tested.

[0097] The test method is: weigh a certain mass of PAO10 and the oil-soluble ionic liquid BTAP888-DOSS-2 synthesized in Example 2, heat to 70°C, stir and mix for 30 minutes, and observe the dissolution of oil-soluble ionic liquids with different mass fractions in PAO10. The results are shown in Table 1.

[0098] Table 1

[0099] BTAP888-DOSS-2 quality score Dissolved state 0.1wt.% Dissolved, transparent 0.3wt.% Dissolved, transparent 0.5wt.% Dissolved, transparent 1.0wt.% Dissolved, transparent 5.0wt.% Dissolved, transparent

[0100] As can be seen from Table 1, the oil-soluble ionic liquid BTAP888-DOSS-2 provided in the present application has good solubility in the base oil PAO10. By using long-chain alkyl quaternary phosphonium cations, the ionic liquid has good oil solubility, which helps to improve the uniformity of the ionic liquid and base oil mixed system, and is beneficial to play a good role in reducing friction, anti-wear and corrosion inhibition on the interface.

[0101] Example 4

[0102] Preparation of ionic liquid lubricating composition 1: Weigh 99.9 g of PAO10 and 0.1 g of the oil-soluble ionic liquid BTAP888-DOSS-2 synthesized in Example 2, heat to 70° C., and stir for 30 min to obtain an ionic liquid lubricating composition 1 with a mass fraction of 0.1%.

[0103] Example 5

[0104] Preparation of ionic liquid lubricating composition 2: Weigh 99.7 g of PAO10 and 0.3 g of the oil-soluble ionic liquid BTAP888-DOSS-2 synthesized in Example 2, heat to 70° C., and stir for 30 min to obtain an ionic liquid lubricating composition 2 with a mass fraction of 0.3%.

[0105] Example 6

[0106] Preparation of ionic liquid lubricating composition 3: Weigh 99.5 g of PAO10 and 0.5 g of the oil-soluble ionic liquid BTAP888-DOSS-2 synthesized in Example 2, heat to 70° C., and stir for 30 min to obtain an ionic liquid lubricating composition 3 with a mass fraction of 0.5%.

[0107] Experimental Example 3

[0108] Thermal stability test of ionic liquid lubricating composition:

[0109] Test method: With base oil PAO10 as a control sample, the thermal stability of the ionic liquid lubricating composition obtained in Examples 4 to 6 and the base oil PAO10 was analyzed using a STA449-F3 (NETZSCH, TGA-DSC) synchronous thermal analyzer.

[0110] The test conditions are: nitrogen atmosphere, heating rate 10°C / min, heating range: room temperature to 600°C. The thermal stability of the ionic liquid lubricating composition is as follows: Figure 1 shown.

[0111] Depend on Figure 1 It is obvious that compared with the base oil PAO10, the decomposition temperature of the ionic liquid lubricating composition is increased, and the amount of ionic liquid provided by the present application added in Examples 4 to 6 is very small, and the mass fraction of the ionic liquid is only between 0.1% and 0.5%. This shows that the addition of a small amount of ionic liquid of the present application can greatly improve the thermal stability of the base oil PAO10, which helps the ionic liquid lubricating composition to form a stable and continuous boundary lubricating film on the friction pair during the lubrication process, so that the ionic liquid lubricating composition can be suitable for lubrication in different temperature environments.

[0112] Experimental Example 4

[0113] Dynamic viscosity and viscosity index test of ionic liquid lubricating composition:

[0114] Test method: The kinematic viscosity and viscosity index of the ionic liquid lubricating composition and the base oil PAO10 were measured using an SVM3000 petroleum product kinematic viscometer produced by Anton Paar of Austria. The results are shown in Table 2.

[0115] Table 2

[0116]

[0117] As can be seen from Table 2, the viscosity index of the ionic liquid lubricating compositions in Examples 4 to 6 is improved compared to that of the base oil PAO10, indicating that the ionic liquid of the present application, as a lubricating additive for the base oil PAO10, can maintain good fluidity at low temperatures and still have sufficient viscosity at high temperatures to form an effective oil film on the surface of the friction pair during the friction process, thereby ensuring sufficient lubrication between the interfaces.

[0118] Experimental Example 4

[0119] Tribological properties test of ionic liquid lubricating composition:

[0120] Test method: The friction and wear performance of the ionic liquid lubricating composition was evaluated using an SRV-IV fretting friction tester produced by Optimol of Germany, and compared with the base oil PAO10.

[0121] The test conditions are as follows: the contact mode of the friction pair is ball-disk contact, the temperature is 25°C, the frequency is 50Hz, the amplitude is 1mm, and the test time is 30min; the upper test ball is a 10mm AISI 52100 steel ball with a hardness of 59-61HRC, and the lower test sample in the steel / steel friction pair is an AISI 52100 steel block with a 24mm diameter, a thickness of 7.9mm, and a hardness of 59-61HRC: the load used in the test is 200N. The wear volume of the lower sample is measured by laser confocal microscopy, and each experiment is repeated at least 3 times, and the average value is taken to obtain the average friction coefficient and average wear volume of the ionic liquid lubricating composition at 25°C as shown in Table 3.

[0122] Table 3

[0123] Average friction coefficient <![CDATA[Average wear volume / 10 -3 mm 3 <!-- 9 -->]]> PAO10 0.22589 2.70211 Example 4 0.17509 1.95948 Example 5 0.11340 0.55105 Example 6 0.11285 0.47344

[0124] It can be seen from Table 3 that compared to base oil PAO10, the average friction coefficient and average wear volume of the ionic liquid lubricating composition are significantly reduced, indicating that the quaternary phosphonium salt ionic liquid of the benzotriazole functionalization provided in the present application has good friction reduction and anti-wear performance, the cation of the oil-soluble ionic liquid provided in the present application is a quaternary phosphonium cation with different alkyl chain lengths of benzotriazole functional groups, and the anion is sodium diisooctyl sulfosuccinate, and the introduction of the benzotriazole group can not only improve the stability of the ionic liquid, but also the π electrons in the benzotriazole and the empty d orbits of the iron surface can form a coordination π-d conjugated effect adsorbed on the substrate surface to form a protective film, which helps the ionic liquid to form a stable lubricating film on the friction pair surface, which is conducive to improving the load-bearing performance of the ionic liquid. And the ionic liquid base oil PAO10 has good oil solubility, which helps the ionic liquid to be fully dissolved in the base oil, and further improves the friction reduction and anti-wear performance of the ionic liquid.

[0125] Experimental Example 5

[0126] Corrosion inhibition performance test of ionic liquid lubricating composition:

[0127] Test method: The corrosion inhibition performance of the ionic liquid lubricant composition obtained in Example 6 was tested using an electrochemical test method. A 1cm×1cm platinum electrode was used as the counter electrode; an iron disk electrode with a diameter of 0.8cm wrapped in epoxy resin (purity>99.99%) was used, leaving an exposed area with a diameter of 0.5cm as the working electrode; saturated calomel was used as the reference electrode to form a three-electrode system. The three-electrode system was immersed in a solution of ethanol:H2O=2:1 (mass ratio). In order to obtain a stable open circuit potential (OCP), record for 60 minutes. The parameters of the potential dynamic polarization (Tafel) are E=Eocp±200mV, and the scanning rate is 0.333mV / s. The results are as follows Figure 2At the same time, the open circuit potential and corrosion current density of the ionic liquid lubricating composition were obtained, as shown in Table 4.

[0128] Table 4

[0129] Open circuit potential / V Corrosion current density / log(i / A) PAO10 -0.3048 -8.23 Example 6 -0.2144 -8.65

[0130] Since the ionic liquid lubricating composition cannot be dissolved in pure water, an ethanol aqueous solution (ethanol: H2O=2:1 (mass ratio)) is used as a solvent and a corrosive medium. Figure 2 The anti-corrosion performance of the ionic liquid lubricating composition on iron in ethanol aqueous solution is shown. Figure 2 The "0.5%" in the table is the mass concentration of the ionic liquid lubricating composition in the ethanol aqueous solution. Figure 2 It can be seen that compared with ethanol aqueous solution, the corrosion current density of the ionic liquid lubricating composition is generally smaller. In general, the greater the corrosion potential, the lower the corrosion tendency, and the greater the corrosion current density, the greater the degree of corrosion. In the experiment, the corrosion potential of the ionic liquid lubricating composition in the ethanol aqueous solution was positively transferred, and the corrosion current density was significantly reduced, showing good corrosion resistance. This shows that the ionic liquid lubricating composition effectively improves the corrosion resistance of iron. The enhancement of corrosion resistance is attributed to the ionic liquid lubricating composition through the π electrons in benzotriazole and the empty d orbits on the iron surface can form a coordination π-d conjugation effect adsorbed on the substrate surface to form a protective film, and the benzotriazole ring and long carbon chain structure unique to the ionic liquid lubricating composition can effectively isolate the corrosive environment, thereby preventing the corrosion of iron.

[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An oil-soluble ionic liquid with anti-corrosion and friction-reducing properties, characterized in that: The oil-soluble ionic liquid has the following general formula: Wherein R and R1 are independently selected from C1-C 18 of alkyl.

2. The oil-soluble ionic liquid with anti-corrosion and friction-reducing properties according to claim 1, characterized in that: The R and R1 are independently selected from any one of methyl, ethyl, propyl, butyl, isobutyl, pentyl, isopentyl, octyl, isooctyl, decyl, isodecyl, dodecyl, tetradecyl, hexadecyl and octadecyl.

3. A method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties, for preparing the oil-soluble ionic liquid according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing chloromethylbenzotriazole, trioctylphosphine and acetonitrile, heating and refluxing to carry out quaternization reaction, and obtaining a crude trioctylphosphonium product functionalized with benzotriazole; (2) washing the crude product of benzotriazole-functionalized trioctylphosphonium with an organic solvent for multiple times to obtain benzotriazole-functionalized trioctylphosphonium; (3) The benzotriazole-functionalized trioctylphosphonium, sodium docusate and acetonitrile are mixed and subjected to an ion exchange reaction to obtain a benzotriazole-functionalized quaternary phosphonium salt ionic liquid, namely the oil-soluble ionic liquid.

4. The method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The molar ratio of the chloromethylbenzotriazole to the trioctylphosphine is 1:1-1.

3.

5. The method for preparing the oil-soluble ionic liquid with anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The conditions of the quaternization reaction are: heating under reflux at 80-85° C. for 24 hours.

6. The method for preparing the oil-soluble ionic liquid with anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The organic solvent used for washing the crude trioctylphosphonium product functionalized with benzotriazole is petroleum ether or n-hexane.

7. The method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The ion exchange reaction is carried out under the conditions of heating at 80-90° C. for 24-48 hours.

8. The method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The molar ratio of the benzotriazole-functionalized trioctylphosphonium to the docusate sodium is 1:1-1.

2.

9. The method for preparing an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties according to claim 3, characterized in that: The ion exchange reaction also includes: After the ion exchange reaction is completed, the crude oil-soluble ionic liquid is obtained, and the crude oil-soluble ionic liquid is subjected to reduced pressure distillation. The obtained heavy phase is dissolved in dichloromethane, washed with water for multiple times, separated into layers, and the obtained organic phase is dried to obtain the benzotriazole-functionalized quaternary phosphonium salt ionic liquid.

10. An application of an oil-soluble ionic liquid having anti-corrosion and friction-reducing properties, characterized in that: The oil-soluble ionic liquid is the oil-soluble ionic liquid described in claim 1 or 2, or an oil-soluble ionic liquid prepared by the preparation method described in any one of claims 3 to 9, and the oil-soluble ionic liquid is used as a lubricating material.

Citation Information

Patent Citations

  • Functionalized oil-soluble ionic liquid and preparing method and application thereof

    CN105254667A

  • Ionic liquid and lubricant composition comprising thereof

    CN106256886A

  • Multifunctional ionic liquid as well as preparation method and application thereof

    CN109503503A

  • Lubricting oil compositions and uses

    US20100093577A1

Cited By

  • Micro-arc oxidation electrolyte and micro-arc oxidation method

    CN119593037A

  • Micro-arc oxidation electrolyte and micro-arc oxidation method

    CN119593037B